Breaking The Language Barrier: A Cross-Cultural Analysis Of Code-Switching in Asian Professional Workplaces - Andi Suwarni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines code-switching practices in Asian professional workplaces, with a specific focus on its linguistic and cultural dimensions. Through a multidisciplinary theoretical framework incorporating Communication Accommodation Theory and Hofstede's Cultural Dimensions, the research investigates how professionals strategically employ code-switching to foster workplace inclusivity, manage hierarchical relationships, and adapt to industry-specific communication demands. The study employs a mixed-methods approach, collecting data through semi-structured interviews with 50 professionals, online surveys (n=200), and 100 hours of workplace observations across various Asian business settings. Results indicate that code-switching serves multiple functions: enhancing communication clarity (87% of respondents), reflecting and reinforcing cultural norms (73%), and mitigating power imbalances in hierarchical structures (65%). The findings underscore code-switching's strategic role in navigating multicultural professional environments, offering practical insights into effective cross-cultural communication strategies and fostering of cohesive professional interactions in Asian workplaces. This research contributes to the growing body of literature on linguistic adaptation in professional contexts and provides practical implications for managing multilingual workplaces in Asia.